Clinical management and survival of patients with central nervous system hemangiopericytoma in the National Cancer Database. (October 2017) - Trifiletti, Daniel M.; Mehta, Gautam U.; Grover, Surbhi; Sheehan, Jason P.
Highlights: 981 patients with central nervous system hemangiopericytomas were evaluated. Multifocal and disseminated disease were associated with inferior survival. Resection and radiotherapy were associated with improved survival. Abstract: Purpose/objectives: Hemangiopericytomas are rare central nervous system (CNS) tumors. We sought to investigate existing clinical management strategies and overall survival (OS) among patients with hemangiopericytomas of the CNS. Methods/materials: All patients diagnosed with CNS hemangiopericytoma from 2004 to 2014 in the National Cancer Database were included. Clinical and treatment-related characteristics were analyzed for an association with OS following diagnosis using univariable and multivariable analyses. Results: Nine-hundred and eighty-one patients were included (0.22% of all CNS tumors). At diagnosis, 22 patients had spinal tumors (2%), 21 patients had multifocal tumors (2%) 28 had disseminated disease (3%), and the remainder were unifocal intracranial tumors. Patients either underwent surgical resection and radiation (48%), surgery alone (37%), radiation alone (6%), or biopsy alone (9%). Of patients with known extent of resection, 53% underwent gross total resection, and, of patients with known radiation modality, 15% received stereotactic radiosurgery. Among the total cohort, 3 and 10 year OS was 87% and 59%, respectively. On multivariable analysis, factors associated with inferior OS included age (HR = 1.05, p  < 0.001), WHO grade ( p  < 0.001), multifocal disease (HR = 2.59, p  = 0.04), disseminated disease (HR = 2.67, p  = 0.01), and chemotherapy (HR = 2.66, p  = 0.01). Patients receiving surgery alone or surgery and radiation demonstrated improved OS compared to biopsy alone (HR = 0.45, p  = 0.01 and HR = 0.47, p  = 0.02, respectively). However radiation utilization did not impact OS ( p  = 0.691). Conclusions: The present data provide large-scale prognostic information from a contemporary cohort of patients with hemangiopericytoma and support an initial attempt at surgical extirpation. The benefits of ionizing radiation are likely limited to improved local control and neurologic function.